At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:First brackets:
(9 : 3) = 3(6 - 7) = (-1)
Next product
4(6 - 7) = 4(-1) = -4
Next sum
(9 : 3) + 4(6 - 7) = 3 + (-4) = -1
Explanation:
Answer:
Answer:First brackets:
(9 : 3) = 3(6 - 7) = (-1)
Next product
4(6 - 7) = 4(-1) = -4
Next sum
(9 : 3) + 4(6 - 7) = 3 + (-4) = -1
Explanation:
B
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.